Developing a systematic approach to training for the agriculture assistants of the Department of Agriculture, Sarawak through action research - Dany, Anak Neb. (1998)
This study focuses on the development of a systematic approach to training for the Agriculture Assistants of the Department of Agriculture, Sarawak. It was conducted through action research. The objectives of the study were to examine the current training system and to suggest ways to improve the system with a view to develop a systematic approach to training for the Agriculture Assistants. The study also attempted to explore the use of action learning concept in the systematic approach to training.